Operative versus nonoperative management of pediatric type 1 open forearm fractures: a retrospective review. Issue 6 (November 2017) - Goss, David A.; Mundy, Andrew; Beebe, Allan C.; Klingele, Kevin E.; Balch Samora, Julie; Samora, Walter P.
Abstract : Background: Considerable debate exists regarding the management of type 1 open forearm fractures in the pediatric population. The purpose of this study was to compare outcomes of nonoperative with operative treatment, and specifically to determine if there are differences in infection rates and complications. Methods: We retrospectively reviewed 155 consecutive type 1 open fractures treated at a single large pediatric hospital from 1995-2013. Inclusion criteria were patients younger than 18 yr of age with type 1 open forearm fractures with a minimum of 6 mo follow-up. Exclusion criteria were patients with type 2 or 3 injuries, inadequate documentation, and less than 6 mo follow-up. Results: From 1995-2013, 19, 455 fractures of the forearm were treated. We identified 185 type 1 open fractures, 30 of which were excluded for inadequate follow-up or documentation. One hundred and nineteen patients were managed nonoperatively, and 36 patients were managed operatively with a mean age of 8.8 and 11.2 yr, respectively. There was a 0% infection rate in the nonoperative group. One patient in the operative group developed an infected nonunion. Initial sagittal deformity for the operative and nonoperative groups was 18.8 and 24.7 degrees. Residual deformity at final follow-up was significantly higher in the nonoperative group in both sagittal ( P =0.031) and coronal ( P =0.017) planes, although all patients fell within accepted parameters. Other than infection rate, there were no differences in complications between the two groups. The overall infection rate was 0.65%, with a 0% infection rate in the nonoperative group. Operations were performed more frequently in older children. Conclusions: Our results indicate that nonoperative management of type 1 open fractures in the pediatric population can be safe and effective.